Plastic and fracture behavior of a dual phase steel sheet under quasi-static and dynamic loadings. (August 2020) - Davaze, Valentin; Vallino, Nicolas; Feld-Payet, Sylvia; Langrand, Bertrand; Besson, Jacques
Abstract: Crack prediction is an important step of car design: its accuracy is crucial to avoid additional development costs and delays. The prediction of steel or aluminium sheets tearing is particularly challenging, and its simulation is not always reliable yet. This could be explained by the use of too simple fracture criteria based on a critical plastic strain that are uncoupled with the constitutive behavior ( i.e.  the material response is not affected by damage). To overcome this problem, coupled damage models are proposed in the literature. To select the appropriate constitutive equations to model the plastic and fracture behavior of a given material, various characterization tests are needed. A comprehensive experimental campaign that covers a wide range of stress states and loading rates was conducted. All tests can be performed on a tensile machine. From the results, an original set of constitutive equations was chosen from the literature to propose an extended Gurson-based damage model. A practical parameter identification procedure is proposed to calibrate the model on a few relevant specimen geometries. The model is then validated on another set of specimen geometries: comparisons between test results and simulations show a good agreement in terms of load–displacement curves for both quasi-static and dynamic loading conditions.